Organomagnesium Crown Ethers and Their Binding Affinities with Li+, Na+, K+, Be2+, Mg2+, and Ca2+ Ions – A Theoretical Study. Issue 33 (2nd September 2021) - Roy, Saikat; Thirumoorthy, Krishnan; Padidela, Uday Kumar; Vairaprakash, Pothiappan; Anoop, Anakuthil; Thimmakondu, Venkatesan S.
Abstract: Novel organomagnesium crown ether molecules have been computationally characterized using density functional theory (DFT). Monomer units of MgC6 are used as building blocks. Isomers of MgC6 H2 have been extensively explored using both DFT and coupled‐cluster methods in the past by some of us. It had been concluded that the seven‐membered ring isomer, 1‐magnesacyclohept‐4‐en‐2, 6‐diyne, was the thermodynamically most stable molecule at all levels. Thus, the latter has been used as the building block for designing new organomagnesium crown ethers. Both alkali (Li +, Na +, and K + ) and alkaline‐earth (Be 2+, Mg 2+, and Ca 2+ ) metal ions selective complexes have been theoretically identified. Theoretical binding energies (▵E at 0 K) and thermally corrected Gibbs free energies (▵G at 298.15 K) have been computed for these molecules with MgC6 ‐6‐crown‐2, MgC6 ‐9‐crown‐3, and MgC6 ‐12‐crown‐4 hosts. Higher binding affinity values obtained for Be 2+ indicate that these new crown ether molecules could effectively be used for Be 2+ encapsulation. Abstract : Binding energytheoretically calculated at various levels shows a selective binding of Li + among alkali metal ions and Be 2+ among alkaline‐earth metal ions